Impact of Subclinical Mastitis-causing Bacterial Species on the Composition and Chemical Properties of Milk - Safak, Tarik; Risvanli, Ali; Asci-Toraman, Zulal (Agricultural Research Communication Centre, 2023)
Background: Here we investigate whether the composition and some chemical properties of milk can correlate with bacterial species causing subclinical mastitis in cows.Methods: One hundred and eighty cows were used in the study. The California Mastitis Test (CMT) was applied to the selected cows. The cows were divided into four groups: cows with negative CMT (n=45), the Escherichia coli (n=45), Streptococcus agalactiae (n=45) and Staphylococcus aureus (n=45) groups.Result: Milk composition and some chemical properties were measured. The highest fat ratio (5.82 +/- 0.34%) was found in the Escherichia coli group (p<0.05). The proportions of solid-non-fat (9.67 +/- 0.09%), protein (3.51 +/- 0.03%), lactose (5.29 +/- 05%) and mineral matter (0.75 +/- 0.01%) were lowest in the Escherichia coli group (p<0.05). The electrical conductivity of milk was lowest in the CMT-negative group (4.23 +/- 0.02 mS/cm), while the Streptococcus agalactiae group had the highest value (4.61 +/- 0.02 mS/cm) (p<0.05). The specific gravity of the Escherichia coli group was lower than the CMT-negative (1,034.91 +/- 0.56 kg/m3) and Staphylococcus aureus (1,034.24 +/- 0.65 kg/m3) groups (p<0.05). Based on our findings, we propose that milk composition and some chemical parameters are altered in subclinical mastitis. However, these could not be standardized according to the responsible bacterial species. We recommend that these parameters are monitored regularly on dairy farms.
Keywords: Bovine mastitis; Chemical properties; Milk composition; Raw milk